-7x+6=76

Simple and best practice solution for -7x+6=76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+6=76 equation:


Simplifying
-7x + 6 = 76

Reorder the terms:
6 + -7x = 76

Solving
6 + -7x = 76

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -7x = 76 + -6

Combine like terms: 6 + -6 = 0
0 + -7x = 76 + -6
-7x = 76 + -6

Combine like terms: 76 + -6 = 70
-7x = 70

Divide each side by '-7'.
x = -10

Simplifying
x = -10

 

See similar equations:

| 3(d-4)+2-2d+1-d= | | (6w+2)-1(8w-3)= | | 3x*x+10x+10=-13x+46 | | x-8=10x+19 | | y-2=2(x+6) | | 8+2y-6=5y+2-2y | | 3+2(5n+6)= | | x*x=2x | | -9a+19a-16a= | | 5x+1=-(x-19) | | -8x-15=-12x+5 | | 4x+2y-7=0 | | 5x*x-42x=27 | | -7q^2+2q+9=0 | | 6(2x-8)=2(6x+4) | | y+5=-(x+3) | | 2x-5=5x+7 | | x(x-8)=4(x-8) | | 3n-7=11 | | 6x-3=69 | | 1.5(x+8)=5.7+0.8x | | 2x+5=9x-58 | | 4(5x-5)=20(x-1) | | 2x(x+6)=3(x-3) | | -30=2 | | -6-8c=3c | | 8x-6y=24 | | (r+4r-3)+1(2r+4)= | | 2x+3y-12=0 | | 6x-13=8x-23 | | 10x*x-50x+40=0 | | 2(4t-2)+t=16-t | | -2x+7=-9 | | -2x-5(3x-13)=-139 | | 12x-10x-27=11 | | 3x+12=3x-42 | | 3=45*3 | | 4x*x-42x-22=0 | | -3p+7=6-(7p+4) | | 3x+12=-3x-42 | | 5x*x=-3x | | -7+3x=-10 | | 4c-2=29 | | 9(y-6)-x^2(y-c)= | | -5(4p+4)-28=4(3p+4) | | 0.20(12)+0.05x=0.10(24+x) | | 7y-6=8 | | 6d-7=3 | | -188-12x+2x=72 | | -4x-2=7x+53 | | 3n-17=67 | | 6-6=9x-4x | | 6x*x+26x=-8 | | 81=3x-6 | | 0.65x+.05(20-x)=.10(58) | | -7x+3=-18 | | 2f-6=4 | | 21x-11=11x-71 | | -3x*x-31x-6=0 | | -102-6x-7x=145 | | -3x*x-31x+22=0 | | 13=4x-11 | | 4k+20=24 | | 2r+4=16r+6 | | 4(k-6)=6(k+2) |